Probiotic supplementation in neonates and long‐term gut colonisation: A systematic review of randomised controlled trials. (11th January 2023) - Srinivasjois, Ravisha; Gebremedhin, Amanuel; Silva, Desiree; Rao, Shripada; Pereira, Gavin
Abstract : Background: Probiotic supplementation in the neonatal period results in improved gut colonisation with probiotic bacteria in the short term. There is limited information on the long‐term sustainability of this colonisation. Aims: To evaluate whether oral probiotic supplementation in the neonatal period results in sustained gut colonisation with probiotic bacteria at or beyond 6 months after its cessation. Methods: A systematic review of neonatal probiotic randomised controlled trials (RCTs) that reported on the stool microbiota during post‐discharge follow‐up was carried out using guidelines of the Cochrane neonatal group. Results: Four RCTs ( n  = 605 infants) were included in the review. The studies were heterogeneous in case selection, choice of probiotics, duration of supplementation, timing and the method of stool microbial analysis. Three RCTs ( n  = 471) showed the presence of intestinal probiotic bacteria at 6‐12 months. The overall certainty of evidence was very low in view of small sample size, heterogeneity and identification only to the genus/species level. Conclusion: Low certainty of evidence suggests that probiotic supplementation in the neonatal period may result in sustained gut colonisation 6‐12 months post‐cessation, but not at 24 months. Adequately powered, well‐designed RCTs with strain‐specific assays are needed in this area.